The Effect of Green Investment on Corporate Behavior - Heinkel, Robert; Kraus, Alan; Zechner, Josef (Journal of Financial and Quantitative Analysis, 2001)
This paper explores the effect of exclusionary ethical investing on corporate behavior in a risk-averse, equilibrium setting. While arguments exist that ethical investing can influence a firm's cost of capital, and so affect investment, no equilibrium model has been presented to do so. We show that exclusionary ethical investing leads to polluting firms being held by fewer investors since green investors eschew polluting firms' stock. This lack of risk sharing among non-green investors leads to lower stock prices for polluting firms, thus raising their cost of capital. If the higher cost of capital more than overcomes a cost of reforming (i.e., a polluting firm cleaning up its activities), then polluting firms will become socially responsible because of exclusionary ethical investing. A key determinant of the incentive for polluting firms to reform is the fraction of funds controlled by green investors. In our model, empirically reasonable parameter estimates indicate that more than 20% green investors are required to induce any polluting firms to reform. Existing empirical evidence indicates that at most 10% of funds are invested by green investors.